Drinking location moderates the association between social group size and alcohol consumption among young adults: An event‐level study. (7th July 2021) - Anderson Goodell, Erin M.; Kuntsche, Emmanuel; Labhart, Florian; Thrul, Johannes
Abstract: Introduction: Previous studies have demonstrated relationships between social and environmental characteristics of the drinking context and alcohol use. However, the use of event‐level data to investigate individual and joint relationships between such characteristics and alcohol use remains a gap in the literature. This study aimed to examine associations between drinking context (location and social group size) and alcohol consumption, and estimate the relationship between the interaction of context and alcohol consumption. Methods: Using an Internet‐based cellphone‐optimised assessment technique, 183 Swiss young adults (mean: 23 years; range: 17–37 years) completed hourly assessments from 8 pm to midnight Thursday through Saturday for five consecutive weeks. Participants contributed 3454 hourly questionnaires. The number of drinks, the number of friends present and location (off‐premise–home, outdoors; on‐premise–bars, restaurants) were assessed based on the previous hour. Multilevel mixed‐effects models were used to assess the relationships of interest. Results: Being off‐premise compared to on‐premise was associated with fewer hourly drinks consumed ( b = −0.44, P < 0.001). Greater numbers of friends present were associated with more drinks consumed ( b = 0.02, P < 0.001). The association between number of friends and number of drinks consumed was significantly stronger for off‐premise compared to on‐premise locations ( b = 0.03, P < 0.001). Discussion and Conclusions: Compared to off‐premise locations, on‐premise locations are associated with more hourly drinks consumed. However, the positive relationship between social group size and drinks consumed is significantly stronger for off‐premise locations compared to on‐premise locations. Findings have implications for tailored interventions focused on reducing alcohol consumption by young adults.